Coordinated operation of distributed energy storage in low carbon networks - Rodrigues,T; Moreira,R; Strbac,G (IEEE, 2018)
Recent developments on climate change regulations are leading to significant changes in the electricity industry with volatility levels and uncertainty increasing significantly. As aresult, systemoperators are extending the procurement of flexibility to end-users and encourage more pro-active behaviors, including provision of system balancing services. In this context, this paper will investigate the potential flexibility and benefits that a coordinated operation of multiple households’ rooftop solar and energy storage can offer to the various sectors of the electricity market. The model will analyze the coordinated operation of multiple households and minimize the supply costs for the whole community while offering flexibility services to the system operator and provide peak demand reduction at the distribution network level. Fundamentally, the proposed model will consider the possibility of households to share energy resources in a peer-to-peer arrangement and thus minimize energy supply costs. In addition, the model also considers the provision of frequency response and reserve services and their associated revenues.Our results have shown significant cost savings can be achieved through a coordinated energy trading and consequently reduce energy transactions with suppliers. Provision offlexibility throughbalancing services becomes the major benefit to support the business case for coordinated operation of storagein low carbon communities.